Frequency of methotrexate intolerance in rheumatoid arthritis patients using methotrexate intolerance severity score (MISS questionnaire) - Fatimah, Nibah; Salim, Babur; Nasim, Amjad; Hussain, Kamran; Gul, Harris; Niazi, Sarah (Clinical rheumatology, 2016)
The objective of the study was to determine the frequency of methotrexate intolerance in rheumatoid arthritis (RA) patients by applying the methotrexate intolerance severity score (MISS) questionnaire and to see the effect of dose and concomitant use of other disease-modifying antirheumatic drugs (DMARDS) on methotrexate (MTX) intolerance. For the descriptive study, non-probability sampling was carried out in the Female Rheumatology Department of Fauji Foundation Hospital (FFH), Rawalpindi, Pakistan. One hundred and fifty diagnosed cases of RA using oral MTX were selected. The MISS questionnaire embodies five elements: abdominal pain, nausea, vomiting, fatigue and behavioural symptoms. The amplitude of each element was ranked from 0 to 3 being no complaint (0 points), mild (1 point), moderate (2 points) and severe (3 points). A cut-off score of 6 and above ascertained intolerance by the physicians. A total of 33.3 % of the subjects exhibited MTX intolerance according to the MISS questionnaire. Out of which, the most recurring symptom of all was behavioural with a value of 44 % whereas vomiting was least noticeable with a figure of 11 %. About 6.6 % of the women with intolerance were consuming DMARDs in conjunction with MTX. Those using the highest weekly dose of MTX (20 mg) had supreme intolerance with prevalence in 46.2 % of the patients. The frequency of intolerance decreased with a decrease in weekly dose to a minimum of 20 % with 7.5 mg of MTX. MTX intolerance has moderate prevalence in RA patients and if left undetected, the compliance to use of MTX as a first-line therapy will decrease. Methotrexate intolerance is directly proportional to the dose of MTX taken. Also, there is no upstroke seen in intolerance with the use of other disease-modifying agents.